2022
DOI: 10.1111/sji.13131
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 immunopathology with emphasis on Th17 response and cell‐based immunomodulation therapy: Potential targets and challenges

Abstract: In December 2019, a novel pneumonia and severe acute respiratory syndrome (SARS) attributed to a new coronavirus infection emerged from Hubei Province, China, and its rapid spread resulted in a global pandemic. 1,2 By the end of November 2021, there were approximately 261 million confirmed total cases of infection with SARS-CoV-2 and more than 5.2 million deaths attributed to coronavirus disease 2019 . This virus spreads via respiratory droplets shed from infected individuals. The average incubation time for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 191 publications
1
18
1
4
Order By: Relevance
“…However, other studies have indicated that Th17 cells can function in the pathogenesis of COVID-19 by inducing cytokine release and Th2 responses, thereby restraining Th1 differentiation and Treg cell proliferation ( 29 ). The Th17-related pro-inflammatory response may be a part of SARS-CoV-2 infection immunopathology, resulting in the development of systemic hyperinflammation ( 30 ). Thus, the reduction of excessive inflammation through the modulation of the Th17 cell differentiation signalling pathway may be an immunomodulatory strategy to relieve COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have indicated that Th17 cells can function in the pathogenesis of COVID-19 by inducing cytokine release and Th2 responses, thereby restraining Th1 differentiation and Treg cell proliferation ( 29 ). The Th17-related pro-inflammatory response may be a part of SARS-CoV-2 infection immunopathology, resulting in the development of systemic hyperinflammation ( 30 ). Thus, the reduction of excessive inflammation through the modulation of the Th17 cell differentiation signalling pathway may be an immunomodulatory strategy to relieve COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Las partículas virales también son reconocidas y presentadas a los linfocitos T CD4+ mediante moléculas del complejo mayor de histocompatibilidad tipo II (MHC II), y una vez activados se convierten en linfocitos T helper 1 (Th1) patogénicos, secretores de citocinas del tipo interferón γ (IFN-γ), interleucina 2 (IL-2) y factor de necrosis tumoral beta (TNF-β). Estas sustancias señalizadoras participan en la activación de macrófagos y en la hipersensibilidad retardada [16,18,19]. Posteriormente, los linfocitos T empiezan a producir y a liberar diferentes citocinas, amplificando la respuesta inmune [6,17].…”
Section: Inmunopatología Del Sars-cov-2unclassified
“…Cursa con una liberación ex-cesiva de citocinas proinflamatorias con el potencial de ocasionar daño multiorgánico y un pronóstico desfavorable para los pacientes. Pueden actuar como mediadores en esta patología pulmonar difusa, induciendo infiltración excesiva de neutrófilos y macrófagos, daño alveolar severo y síndrome de distrés respiratorio agudo (SDRA) [17,18].…”
Section: Tormenta De Citocinasunclassified
See 2 more Smart Citations